Performance Management System (PMS) in a Malaysian local government: a New Institutional Sociology (NIS) perspective - Hasbolah, Farhana; Mohd Alwi, Norhayati; Mohamad, Muslim Har Sani (2012)
Key Performance Indicators, also known as KPI, help an organization to define and measure progress toward organizational goals. It is one of examples of private sector practice developed and implemented in public sector organizations to improve the performance of public services. The system is supposed to assist the government meeting its objectives as well as to make it become more accountable. This explanatory case study intends to investigate the evolution of performance management system in a Local Government (LG) in Malaysia. New Institutional Sociology (NIS) is used to understand the various institutional pressures faced by the organization during the process of developing and implementing KPIs. It has been found that KPIs were used as a complementary tool to the existing PMS practiced within the organization which is Annual Work Target (AWT). AWT which has become shared values within the organization, is still been using as the prime PMS despite of its drawbacks. Supposedly, KPIs being new PMS was to play its role to inculcate a high performance culture. The study has also discovered that the new PMS brought several changes to the individual, departments, and organization itself. Apart from that, the study was able to discover and point out the changes in organizational behavior among the organizational members through the implementation KPIs. This study gives a new insight to the Public Sector Accounting research by exploring the development and implementation of KPIs in a LG as well as the organizational changes within the organization.